An approach for the synthesis of 2-aryl-3-sulfonyl substituted quinolines through an electrochemical cascade annulation pathway. Issue 11 (25th May 2022) - Ma, Qiang; Li, Ming; Chen, Zhuo; Ni, Shao-Fei; Wright, James S.; Wen, Li-Rong; Zhang, Lin-Bao
Abstract : An electrochemical protocol for the synthesis of 2, 3-disubstituted quinolines by reacting benzoxazinones with arylsulfonyl hydrazides was established under simple and mild conditions (room temperature and an undivided cell). Abstract : An electrochemical protocol for the synthesis of 2, 3-disubstituted quinolines by reacting benzoxazinones with arylsulfonyl hydrazides was established under simple and mild conditions (room temperature and an undivided cell). The methodology does not require noble catalysts or external oxidants, providing a green and mild pathway for de novo synthesis of functional quinolines with excellent regioselectivity. Moreover, the method tolerated a variety of functional groups. Notably, the scaled-up experiment and follow-up procedures demonstrate the practicality of electrochemical synthesis.